2021
DOI: 10.17221/665/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interspecific competition on crop yield and nitrogen utilisation in maize-soybean intercropping system

Abstract: Intercropping system plays a crucial role in improving crop yield, nitrogen utilisation efficiency (NUE) and economic benefit. The difference in crop yield and interspecific relationship under different bandwidth and row ratio allocation patterns are still unclear. A field experiment was carried out to explore change regularities between crop yield and interspecific relationships under maize soybean intercropping with different bandwidths and row ratios. The results showed that the yield of intercropped crops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Soil amended with dolomite exhibited a higher TN 2 -fixation than TN DFS , whereas soils with greater nutrient content, such as those observed with the combined charcoal and compost treatment, exhibited a lower TN 2 -fixation than TN DFS (Table 2). This study revealed that when access to soil N is limited, legumes can meet their N demand through N 2 -fixation, as found in the previous study by Lambers et al [52].…”
Section: Nitrogen Fixation By Centrosemasupporting
confidence: 84%
“…Soil amended with dolomite exhibited a higher TN 2 -fixation than TN DFS , whereas soils with greater nutrient content, such as those observed with the combined charcoal and compost treatment, exhibited a lower TN 2 -fixation than TN DFS (Table 2). This study revealed that when access to soil N is limited, legumes can meet their N demand through N 2 -fixation, as found in the previous study by Lambers et al [52].…”
Section: Nitrogen Fixation By Centrosemasupporting
confidence: 84%
“…In contrast, sugarcane–peanut intercropping (IS treatment) increased soil N availability and promoted microbial growth and metabolism, particularly in bulk soil. Taken together, the differences in microbial C and P limitation across crops might be explained by the interspecific competition on soil N in the intercropping system (Feng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with sole crop, on the one hand, the increase in soil nutrient and root-derived C (root exudates) induced by intercropping might alleviate microbial C and nutrient limitation by increasing fertilizer use efficiency (Steinauer et al, 2015 ; Tang X. Y. et al, 2021 ). On the other hand, intercropping-induced frequent interactions in root–soil–microbes systems and fast-growing microbes appear to enhance nutrient competition between microbes–microbes and microbes–crops, which is likely to regulate microbial C and nutrient limitation (Hilbig and Allen, 2015 ; Kuster et al, 2016 ; Feng et al, 2021 ). It is therefore essential to explore the intercropping effects on microbial C and nutrient limitation, which could further affect soil nutrient uptake and plant biomass productivity and yields (Tang X. Y. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intercropped maize provides equal yields or minimal yield losses compared with monoculture maize, whereas increased additional soybean yields can be obtained, providing additional income compared with maize alone (Iqbal et al., 2018). Maize strips contain two rows with a distance of 40 cm, and the two rows of maize are all border rows, which will amplify the maize yield in border rows (Feng et al., 2021). Soybean strips consist of four rows of soybean with a row‐to‐row distance of 40 cm.…”
Section: Discussionmentioning
confidence: 99%